Strategies for controlling nucleation and crystal growth in membrane distillation crystallisation. - Ouda, Alaa Samir (Cranfield University, 2023)
Membrane distillation crystallisation (MDC) is a promising technology that can address the primary restriction of regulating supersaturation rate in conventional crystallisation technologies, thus affording good control over nucleation and crystal growth. The supersaturation rate (R’) was used as a key parameter to govern the onset of nucleation (induction time) instead of irreversible flux decline, which is typically used in previous MDC studies. In this work, in-line turbidimetry enabled the precise determination of the induction time and metastable zone width (MSZW), which have been correlated to the supersaturation rate for a detailed characterisation of the nucleation kinetics and growth mechanism. The supersaturation at which nucleation occurred was measured within the interfacial boundary layer and bulk solution to differentiate between two scaling mechanisms (crystal adhesion or deposition) associated with the underlying nucleation mechanism based on classical nucleation theory. This allowed the MDC to decouple surface scaling from bulk nucleation at specific MSZW regions where the achieved crystallisation trajectory could balance between crystal quality and reduced membrane scaling. The increased supersaturation rate independent of the boundary layer enabled the transition towards a homogeneous nucleation mechanism where scaling is minimised, which aligns with classical nucleation theory but contradicts previous MDC studies. The consistent and reproducible nucleation kinetics obtained in this study while controlling multiple supersaturation factors suggested crystallisation to be inherently scalable, which is a unique facet compared to conventional crystallisers. Furthermore, the ability to sustain the supersaturation profile following nucleation enabled the system to reposition the crystallisation trajectory close to the MSZW threshold, providing high potential for nucleation kinetic control while regulating crystal size, size distribution and yield. Therefore, the kinetic framework established in this work offers advanced control over the nucleation mechanism and growth phase, which can be employed to fulfil commercial requirements for zero liquid discharge and more valuable crystalline products.
Bajón Fernández, Yadira - Associate Supervisor
Keywords: Hollow fibre; Nucleation; Crystal growth; Scale-up; Induction time; MSZW; Scaling